2008 2nd International Symposium on Advanced Networks and Telecommunication Systems 2008
DOI: 10.1109/ants.2008.4937777
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of the WiMedia MAC protocol in high density wireless environments

Abstract: Wireless networks based on the WiMedia specifications provide a good way to build low cost and robust networks with considerably high data rates. This work investigates the limits of these networks, especially in terms of scalability and time behavior. With a WiMedia MAC (media access control) protocol simulator we analyzed scenarios with up to 80 simultaneous nodes per channel and identify situations where the efficiency of the protocol degrades. The simulations are followed by an investigation of the situati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In previous research [12] we showed that networks with large beacon groups the startup phase of the network can take minutes, until all nodes have allocated a valid beacon slot and the beacon period contraction algorithm has come to an end. Also topology changes will require a long time.…”
Section: Differences Of Wimedia and Ieee 80211mentioning
confidence: 99%
“…In previous research [12] we showed that networks with large beacon groups the startup phase of the network can take minutes, until all nodes have allocated a valid beacon slot and the beacon period contraction algorithm has come to an end. Also topology changes will require a long time.…”
Section: Differences Of Wimedia and Ieee 80211mentioning
confidence: 99%